Use of artificial pots by Melipona fasciculata Smith, 1854 (tiúba) for honey production in different models of beehives (Research, Society and Development, 2020)
Despite its high value and production potential, meliponiculture lacks technological practices that improve the product extraction process. This study aimed to compare the acceptance of artificial pots by Melipona fasciculata in the production of honey in different models of hives. The experiment was carried out between the months of August and December 2017, in the village of Limoeiro, municipality of Viana, Baixada Maranhense (Brazil). Artificial acrylic pots (50ml) were used in honey supers of different hive models (PNN, MARTHI, EMBRAPA). Acceptability and honey production were observed within the artificial pots. Monthly, the full and closed pots were removed and sent to the Laboratory, being replaced by empty artificial pots. Results indicated greater acceptance of artificial pots by bees in the EMBRAPA hive model. In the similarity dendrogram, based on Bray-Curtis distances, there was a strong clustering (95%) between the PNN and MARTHI hives, with the EMBRAPA model being the most dissimilar. The production of honey in artificial acrylic pots can be a practical, hygienic and economical alternative, being an innovative way to produce and consume honey.